1975
DOI: 10.1002/ijc.2910150605
|View full text |Cite
|
Sign up to set email alerts
|

Tumour inhibition mediated by BCG in immunosuppressed rats

Abstract: Two rat sarcomas (CC5 and P7) which grow progressively on transplantation into normal syngeneic hosts failed to develop when injected in admixture with the Glaxo strain of Bacillus Calmette-Guérin (BCG). Under comparable conditions, the local development of a third neoplasm (P8) was temporarily inhibited and the number of pulmonary metastases significantly reduced. Experiments were undertaken to determine the extent to which the anti-tumor action of BCG required an immunocompetent host. Rats were immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0

Year Published

1976
1976
1984
1984

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
(13 reference statements)
2
10
0
Order By: Relevance
“…In the present studies, the level of immunosuppression produced by simple whole body irradiation has not been characterized, but it has been clearly demonstrated that irradiated animals, while rejecting mixed inocula of cells + BCG, fail to develop the systemic tumour immunity normally capable of controlling a simultaneous challenge with tumour cells alone. The present findings and those of Moore et al (1975) demonstrate, therefore, that fundamentally different host responses are involved in these two events and that full host immunocompetence is not necessary for BCG contact therapy. This is further supported by the previous demonstration of BCG contact suppression of rat tumour xenografts in athymic nude mice (Pimm and Baldwin, 1975).…”
supporting
confidence: 58%
See 4 more Smart Citations
“…In the present studies, the level of immunosuppression produced by simple whole body irradiation has not been characterized, but it has been clearly demonstrated that irradiated animals, while rejecting mixed inocula of cells + BCG, fail to develop the systemic tumour immunity normally capable of controlling a simultaneous challenge with tumour cells alone. The present findings and those of Moore et al (1975) demonstrate, therefore, that fundamentally different host responses are involved in these two events and that full host immunocompetence is not necessary for BCG contact therapy. This is further supported by the previous demonstration of BCG contact suppression of rat tumour xenografts in athymic nude mice (Pimm and Baldwin, 1975).…”
supporting
confidence: 58%
“…The present findings and those of Moore et al (1975) demonstrate, therefore, that fundamentally different host responses are involved in these two events and that full host immunocompetence is not necessary for BCG contact therapy. This is further supported by the previous demonstration of BCG contact suppression of rat tumour xenografts in athymic nude mice (Pimm and Baldwin, 1975).…”
supporting
confidence: 58%
See 3 more Smart Citations